2001
DOI: 10.1002/lsm.1036
|View full text |Cite
|
Sign up to set email alerts
|

Histologic evaluation of skin damage after overlapping and nonoverlapping flashlamp pumped pulsed dye laser pulses: A study on normal human skin as a model for port wine stains

Abstract: Reasoning that the mechanism of tissue injury is comparable for normal and PWS skin, we conclude that it is safe to treat PWS with overlapping FPPDL pulses to achieve homogeneous lightening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 9 publications
2
20
0
1
Order By: Relevance
“…This study reports an increase in the RBC coagulation depth from approximately 1.0 to 1.5 mm at 8 J/cm 2 to the maximum depth of the dermis at approximately 2.5 mm at radiant exposures of 23 to 30 J/cm 2 . The depth of RBC coagulation agrees well with similar studies 13 that found a maximum vascular damage depth of 1.8 mm at 8 J/cm 2 . The maximum RBC coagulation depth measured in this study may have been much larger if the dermis were thicker.…”
Section: Light-skinned Individuals (Groups 1 and 2)supporting
confidence: 81%
See 2 more Smart Citations
“…This study reports an increase in the RBC coagulation depth from approximately 1.0 to 1.5 mm at 8 J/cm 2 to the maximum depth of the dermis at approximately 2.5 mm at radiant exposures of 23 to 30 J/cm 2 . The depth of RBC coagulation agrees well with similar studies 13 that found a maximum vascular damage depth of 1.8 mm at 8 J/cm 2 . The maximum RBC coagulation depth measured in this study may have been much larger if the dermis were thicker.…”
Section: Light-skinned Individuals (Groups 1 and 2)supporting
confidence: 81%
“…[8][9][10] Although motivation exists to increase radiant exposures, the degree of vascular damage selectivity decreases as higher radiant exposures increase the risk of damage to the epidermis 8,9,11,12 and perivascular tissues. 13,14 The epidermis offers a competing site for light absorption by melanin, 15 resulting in nonspecific heating therein and subsequent blistering and dyspigmentation. As heat diffuses out of the dermal blood vessels into the adjacent tissue, perivascular collagen damage can also occur, especially near the lesion's surface, where fluence levels are much higher than at deeper depths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…También se han observado buenos resultados en casos resistentes administrando un doble pase en la misma zona, usando primero una longitud de onda y una duración de pulso de 590-600 nm y 1,5 ms, respectivamente, y después un segundo pase para eliminar los vasos más superficiales a 585 nm y 450 µs 45 . En otro estudio experimental en esta misma línea, realizado sobre piel sana, observan que el solapamiento de impulsos se asocia a una mayor penetrabilidad, sin que se asocie una mayor incidencia de daño de otras estructuras como la epidermis 46 .…”
Section: Malformaciones Capilaresunclassified
“…Additionally, most of these clinical studies limit the fluences used to 10 J/cm 2 . A few studies report the histological analysis of vasculature in response to irradiation by lasers that are currently used in clinical practice [9,[34][35][36][37]. The second goal of this study was to provide additional morphological and apoptotic histological analysis and correlate the resulting laser-induced purpura to vascular damage.…”
Section: Introductionmentioning
confidence: 99%